(untitled) (Baghdad Science Journal, 2021)
Each Intensity Modulated Radiation Therapy (IMRT) plan needs to be tested and verified before any treatment to check its quality. Octavius 4D-1500 phantom detector is a modern and qualified device for quality assurance procedure. This study aims to compare the common dosimetric criteria 3%/3 mm with 2%/2 mm for H&N plans for the IMRT technique. Twenty-five patients with head and neck (H&N) tumor were with 6MV x-ray photon beam using Monaco 5.1 treatment planning software and exported to Elekta synergy linear accelerator then tested for pretreatment verification study using Octavius 4D-1500 phantom detector. The difference between planned and measured dose were assessed by using local and global gamma index (GI) analysis method at threshold 10%. The DD/DTA criteria are performed with 3%/3 mm and 2%/2 mm. A significant difference is shown between the measured and calculated point dose for the treatment plans. A comparison made between the gamma passing rate between the 2%/2 mm and 3%/3 mm shows a significant difference for local and global which shows that the 2%/2 mm are more sensitive to dose variation than 3%/3 mm. The total monitor unit (MU) shows a negative linear relationship with both criteria and %GP types. A significant correlation is shown between the total MU and global %GP at 2%/2 mm criterion. The conclusion of the study indicates that 2%/2 mm criterion is more sensitive to the dose distribution changes than the 3%/3 mm. The total number of monitor units should be taken into consideration during the planning of H&N tumors using the IMRT plans.